Analysis on the Income Tax Compliance Behavior of Muzaki at Lazismu Sragen - Arvie Johan; Dito Karisma Prasetyo (Universitas Ahmad Dahlan, 2022)
Introduction to The Problem: Zakat as a deduction of taxable income has become an issue that has attracted the attention of the public economy. The most obvious thing is that the low realization of zakat collection and tax ratios affect the welfare gap (distribution function) and public services received by the citizens (allocation function). On an extreme scale, non-compliance with zakat and tax may threaten social cohesion and legal authority.Purpose/Objective Study: This study aims to find out how zakat regulation as a deduction of taxable income affects muzaki's behavior to comply or not comply with tax obligations.Design/Methodology/Approach: The research design is empirical legal research with qualitative analysis. The primary source builds on focus group discussions (FGDs). Otherwise, secondary sources are collected through a literature study of primary, secondary, and tertiary legal materials.Findings: Zakat as a deduction of taxable income affects muzaki's behavior to comply with tax obligations. The zakat scheme as a deduction of taxable income greatly influences muzaki's behavior within the level of tax compliance, specifically the level of resistance to tax because the system is considered oppressive, to move up to the level of tax compliance trying to comply but having difficulty understanding tax. This significant change occurs because the Zakat scheme as a deduction of taxable income is able to eliminate the characteristic of “tax is conflicting with zakat” in the level of tax compliance resistance because the system is considered oppressive.Paper Type: Research Article.